2021
DOI: 10.3389/fpsyt.2021.667602
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Disorders and Impact on Quality of Life in Patients With Pulmonary Arterial Hypertension

Abstract: Objective: Mental health may affect the quality of life (QoL) in patients with pulmonary arterial hypertension (PAH). However, mental disorders have not been systematically assessed in these patients. We examined the prevalence of mental disorders using structured interviews and determined their impact on QoL in patients with PAH.Methods: This study included 217 patients with PAH from two German referral centers. Psychiatric disorders were assessed using the structured clinical interview for DSM-V. QoL was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 25 publications
1
38
0
1
Order By: Relevance
“…Our study also found similar results: 70.09% of patients were judged to have depressive symptoms on the depression score, and 28.22% had moderate to severe depression. The result of the high incidence of depressive symptoms in present study was consistent with a previous study in Beijing, China (11), and in other countries (12). These may be because of the poor prognosis, significant side effects, and activity limitations of patients diagnosed of PAH that may expose patients to higher stressors, leading to the development of depression and anxiety (21).…”
Section: Anxiety and Depression Symptoms Of Patients With Pahsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also found similar results: 70.09% of patients were judged to have depressive symptoms on the depression score, and 28.22% had moderate to severe depression. The result of the high incidence of depressive symptoms in present study was consistent with a previous study in Beijing, China (11), and in other countries (12). These may be because of the poor prognosis, significant side effects, and activity limitations of patients diagnosed of PAH that may expose patients to higher stressors, leading to the development of depression and anxiety (21).…”
Section: Anxiety and Depression Symptoms Of Patients With Pahsupporting
confidence: 91%
“…For example, a study in Japan reported 64% of candidates had depression and 28% had anxiety (10). A study in Beijing, China, found 66.3% of samples had depression and anxiety (11), while 38.2% of PAH patients reported these symptoms in Germany (12). Some studies also have suggested that patients' anxiety and depression symptoms may further lead to deterioration of physical function (11,13), poor cardiac function (14), poor prognosis (11), worsening quality of life, and increased health-related costs (10).…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed a limited impact of the Covid-19 pandemic on anxiety, depression and QoL in patients with PAH. Olsson identified higher prevalence of depression and panic disorder in patients with PAH contributing to impaired QoL ( 18 ). Psychological distress in PAH results from impact on daily life due to physical limitations, unclear prognosis and unemployment ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…This prospective, exploratory observational multicenter study included patients with confirmed PAH of a cohort previously described in the PEPPAH-study ( 18 ), at two participating PH referral centers (Hannover Medical School and University of Giessen, both in Germany). This study was conducted from May 7th, 2020 to August 4th, 2020 by a self-administrated questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation